2018
DOI: 10.1166/jamr.2018.1401
|View full text |Cite
|
Sign up to set email alerts
|

Applied Histological and Chemical Analysis for Detection of Adulteration of Minced Meat and Sausage

Abstract: Meat and meat products were undergone to adulteration due to its high price and cause many diseases and economic losses for consumers. Fifty samples of minced meat and sausage (25 each) were collected randomly from supermarkets in Assiut city. The samples were subjected to histological and chemical analysis for detection of adulteration. Histologically, adulteration was detected in minced meat and sausage by addition of smooth muscle fibers of hollow organs, heart muscles, spongy bone, thyroid glands, adipose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Glandular and nervous tissues were also detected in cured sausage samples in a study conducted by Malakauskiene et al [13] in Lithuania. In a study of Mokhtar et al [14] conducted in Egypt, adulteration was determined in 88% of minced meat and 100% of sausages, similar to this study bone, cartilage, smooth muscle fibers, nerve cells, tendon were present in sausages.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Glandular and nervous tissues were also detected in cured sausage samples in a study conducted by Malakauskiene et al [13] in Lithuania. In a study of Mokhtar et al [14] conducted in Egypt, adulteration was determined in 88% of minced meat and 100% of sausages, similar to this study bone, cartilage, smooth muscle fibers, nerve cells, tendon were present in sausages.…”
Section: Discussionsupporting
confidence: 82%
“…In many countries including Turkey, soya is in the list of substances that cause allergies, and it is a legal requirement to be indicated on the product's label [21,22]. Poppy seed was determined similar to the study conducted by Mokhtar et al [14] in addition to paprika and allspice, which are frequently used by fermented sausage producers in Mardin (Turkey). Addition of tissues such as central nervous system, a possible vector of infective agents, [8,11,20] may cause health problems and use of plant-derived ingredients in sausages without specifying at the label is not legally permitted because of their possible allergic effects [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous researchers have shown that the use of histological methods in combination with routine methods would give more accurate results when evaluating meat quality (Horn and Seidler, 1978;Ugurlu, 1991;Tremlova and Starha, 2003;Mokhtar et al, 2018). These studies have shown that histological methods are one of the most accurate ways to determine various tissues in fermented sausages because they give a comprehensive view of the components that are part of the product.…”
Section: Introductionmentioning
confidence: 99%